Molecular relationships within Bostrychia tenuissima (Rhodomelaceae, Rhodophyta) - Zuccarello, Giuseppe C.; West, John A.; Karsten, Ulf; King, Robert J. (Phycological research, 1999)
SUMMARY Bostrychia tenuissima King and Puttock is restricted to southern Australia and New Zealand. Previous studies in Australia have revealed two distinct patterns in the presence of osmotically active polyols. Southern populations only have D‐sorbitol whereas northern populations have both D‐sorbitol and D‐dulcitol. These polyol patterns lead to speculation on the ecotypic differentiation of these two population types. Using single‐stranded confirmation polymorphism to rapidly score plastid haplotypes, plus DNA sequencing, a 100% congruence was found between polyol patterns and plastid haplotype. Analysis of 33 B. tenuissima isolates shows that the plastid relationships closely follow biogeo‐graphic regions, with south‐eastern Australia (southern NSW and Victoria) and South Australia and Tasmania having one haplotype and central and northern NSW having two alternate haplotypes. There is an overlap at the haplotype boundary just south of Sydney, New South Wales.